Increased terrestrial to ocean sediment and carbon fluxes in the northern chesapeake bay associated with twentieth century land alteration - Saenger, C.; Cronin, T. M.; Willard, D.; Halka, J.; Kerhin, R. (Estuaries and Coasts, 2008)
We calculated Chesapeake Bay (CB) sediment and carbon fluxes before and after major anthropogenic land clearance using robust monitoring, modeling and sedimentary data. Four distinct fluxes in the estuarine system were considered including (1) the flux of eroded material from the watershed to streams, (2) the flux of suspended sediment at river fall lines, (3) the burial flux in tributary sediments, and (4) the burial flux in main CB sediments. The sedimentary maximum in Ambrosia (ragweed) pollen marked peak land clearance (similar to 1900 A.D.). Rivers feeding CB had a total organic carbon (TOC)/total suspended solids of 0.24 +/- 0.12, and we used this observation to calculate TOC fluxes from sediment fluxes. Sediment and carbon fluxes increased by 138-269% across all four regions after land clearance. Our results demonstrate that sediment delivery to CB is subject to significant lags and that excess post-land clearance sediment loads have not reached the ocean. Post-land clearance increases in erosional flux from watersheds, and burial in estuaries are important processes that must be considered to calculate accurate global sediment and carbon budgets.
id: 812; 316CY Times Cited:1 Cited References Count:54Y